2009
DOI: 10.1186/1471-2474-10-32
|View full text |Cite
|
Sign up to set email alerts
|

Arm rotated medially with supination – the ARMS variant: description of its surgical correction

Abstract: Background: Patients who have suffered obstetric brachial plexus injury (OBPI) have a high incidence of musculoskeletal complications stemming from the initial nerve injury. The presence of muscle imbalances and contractures leads to typical bony changes affecting the shoulder, including the SHEAR (Scapular Hypoplasia, Elevation and Rotation) deformity. The SHEAR deformity commonly occurs in conjunction with Medial Rotation Contracture (MRC) of the arm. OBPI also causes muscle imbalances at the level of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…We have published extensively the effectiveness of triangle tilt surgery in correcting glenohumeral joint incongruity and thereby improving upper extremity functions in OBPP patients[20-28]. Here, we show both functional and anatomical improvements significantly after triangle tilt and or mod Quad as revision surgeries in 20 OBPP patients, who had other surgical treatments at outside clinics before visiting our clinic for further treatment.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…We have published extensively the effectiveness of triangle tilt surgery in correcting glenohumeral joint incongruity and thereby improving upper extremity functions in OBPP patients[20-28]. Here, we show both functional and anatomical improvements significantly after triangle tilt and or mod Quad as revision surgeries in 20 OBPP patients, who had other surgical treatments at outside clinics before visiting our clinic for further treatment.…”
Section: Introductionmentioning
confidence: 57%
“…Eighteen OBPP children, who had shoulder joint incongruency and SHEAR undergone TT bony operation with us. We demonstrated that this procedure effectively addressed the bony deformities of the affected upper extremity and improved it’s anatomy and functions[20-28]. After undergone these two revision surgical procedures with us, these twenty patients had better results both functionally and anatomically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The affected arm, forearm, and hand are shorter than the normal side, and the degree of shortening appears to be related to the severity of neurological damage (Uysal et al 2007 ). Often a fi xed internal rotation deformity is associated with SHEAR in obstetric palsy (Nath et al 2009 ). These include paresis, muscle contracture, co-contraction of antagonistic muscles, and deformities.…”
Section: Obstetric Brachial Plexus Palsymentioning
confidence: 99%
“…Nerve repair, modified Quad, and triangle tilt surgeries were performed on these patients by the senior author and the surgeon (Nath RK) as described previously [8][9][10][11] . Information regarding finger movement was obtained from the patient's parent or guardian during the initial evaluation.…”
Section: Studymentioning
confidence: 99%